(untitled) (World Science, 2020)
In the article it is defined the notion of musical policy as a consistent concept of state activities which influence the support and development of music, music education, music facilities, economics of music life etc. The constituent parts of the music policy of modern Germany are determined. It is analyzed the impact and the importance of Leo Kestenberg’s reformation activity for the development of the music policy of Prussia in the 1920s, it is explained the role of the music policy in modern FRG and its overall state control of the country’s music life in particular. It is outlined a strategic direction of the activity of German Music Council (GMC; Deutsche Musikrat –DMR) – organization of music life and formation of the music policy in a new social context. It is established that the music policy is also a social policy which strives for preservation of general national state interests. The tasks and directions of the implementation of the music policy of FRG are singled out.